4x2+4x-8 4(x2+x-2) and (4x+8)(x-1)
4x2 - 23xy + 15y2 = (4x - 3y)(x - 5y)
-((4x + 1)(x - 1))
ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X
4x2-4x-120 = (2x+10)(2x-12) when factored
4x2+4x-8 4(x2+x-2) and (4x+8)(x-1)
4x2 - 4x + 2xy - 2y = 4x(x - 1) + 2y(x - 1) (4x + 2y)(x - 1).
4x2 - 23xy + 15y2 = (4x - 3y)(x - 5y)
(2x + 3)(2x - 1)
-((4x + 1)(x - 1))
2(2x^2 + 2x - 5)
ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X
4x2-4x-120 = (2x+10)(2x-12) when factored
4x2-4x-120 = (2x+10)(2x-12) when factored
If you can't factor it easily, use the quadratic formula.
That doesn't look quite right. As written, that's 4x + 61, which doesn't factor. If you meant 4x2 + 49x + 12, the answer is (4x + 1)(x + 12)
4x2 + 8x + 4 = 4 (x2 + 2x + 1) = 4 (x + 1)2